Belok Kiri Langsung Pada Saat Lampu Merah - Bambang Ismanto Siswosoebrotho (The Institute for Research and Community Services, Institut Teknologi Bandung, 1997)
Belok Kiri Langsung (BKL) pada saat lampu lalu lintas menyala merah or Left Turn on Red (LTOR) on any road intersection is now confusing some drivers in this country who do not know or have never known the traffic related regulation. Indonesian Road Traffic and Transportation Law (UU No. 15/1992) with its Goverment Decrees established and issued by the President concerning the Infrastructure and Road Traffic, Peraturan Pe,erintah (PP) No. 43, 1993, article 59 paragraph 3 says that vehicles in any approach which has an LTOR sign displayed may turn left after stopping, providedit is safe to do so. The Indonesian Road Traffic and Transportation Law, UU No. 14/1992 and PP 43/1993 art. 59 p(3) provides the authority for its use. The following problem arises, that the BKI, can not be done safely on any road intersections. Many intersections have geometry deficiencies, such as lack of channelisation, lack of turning lanes, absence of sidewalks and insufficient intersection areas. On the road ontersection within the Area Traffic Control System (ATCS), this problem becomes more difficult since LTOR is not only involves in installing traffic signs, but modification on controler and detector which affect the lanes presence timed calls may required before LTOR is permitted.